PENGEMBAGAN MEDIA E-BOOKLET MENGENAI DIET SEIMBANG SEBAGAI UPAYA PENCEGAHAN DIABETES MELITUS TIPE 2 PADA GURU (DI PGTK ANAK CERIA BANDUNG) - Zahrinafirdaus, Putrie Amanda; Setiawan, Ridwan (Politeknik Kesehatan Kemenkes Bandung, 2024)
Background: The prevalence of DM sufferers in 2022 is 644,704 people with an average annual value of 874,422.75 in the last 4 years who suffer from DM. The highest incidence of DM in Bandung City in 2022 was in Arcamanik, Central Antapani District at 40.78% (18,527 people). For this reason, preventive measures are needed, one of which is education (health education). Objective: Develop a Balanced Diet e-Booklet media as an effort to prevent diabetes mellitus among teachers at PGTK Anak Ceria Bandung which is suitable for use as a health education media. Method: research method applies the ADDIE methodology to research and development techniques. The total population is 18 teachers at PGTK Anak Ceria Bandung. Results: The Balanced Diet e-Booklet media is in the form of a digital book which is uploaded via the heyzine.com page. Obtained a score of 94. 2% in the Material Experts' very good category and 96.2% in the Media Experts' very decent category. Using the Balanced Diet e-Booklet media has a 63% boost in influence. Conclusion: The Balanced Diet e-Booklet media is in the form of a digital book. The media was declared very good and very appropriate by the Expert and there was an influence of providing the Balanced Diet e-Booklet media to teachers at PGTK Anak Ceria Bandung.